Design & Analysis of Stress on Drill Bit - et. al., Swapnil Choudhary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The manufacturing sector of India mainly depends on its productivity and quality. In many manufacturing activities, drilling is an ordinary operation that forms the main machining cost. This paper reviews development in drill bit with available geometric properties, materials for a drill bit, and coatings. For the lowest machining cost and highest profit rate, it's a difficult task to select the best tool with its cutting parameters. With a slight improvement in drill bit geometric properties, we can minimize stress and improve the tool's quality and life. This paper will compare the stress generated over drills by making certain changes in drill geometric properties such as point angle. Drill with lower stress shows longer tool life. Micro drill with point angle 1160 shows less stress distribution. Micro drills with lower stress will have longer tool life. Two different materials as Alpha titanium alloy and Beta titanium alloy used for analysis. We got the different results with parameters, from that the beta titanium alloy is best, which comes in the nearby comparison with HSS. Comparison between alpha and beta titanium alloy is done with HSS based on their equivalent stress, strain, and deformation.